Relationship between bone remodeling markers, bone mineral density, and severity of coronary atherosclerosis in men with stable coronary heart disease - T. A. Raskina; M. V. Letaeva; A. V. Voronkina; E. B. Malyuta; O. N. Khryachkova; O. L. Barbarash (Современная ревматология)
The development of atherosclerosis is a complex multifactorial process, in which the markers of bone formation and resorption play an important role and which is closely related to the calcification of the vessel intima and fibrous plaques.Objective: to assess the relationship between bone remodeling markers (cathepsin K, C-terminal telopeptide of type I collagen (CTX-I) and osteopontin), bone mineral density (BMD), and severity of coronary atherosclerosis in men with stable coronary heart disease (CHD).Patients and methods. The investigation enrolled 102 male patients with verified stable CHD. Coronary angiographic and densitometric findings and blood cathepsin K, osteopontin, and CTX-I concentrations were assessed.Results.The concentration of cathepsin K and CTX-I was significantly higher and that of osteopontin was significantly lower in patients with CHD than in men without CHD. There was no association of the level of bone remodeling markers with the type of coronary artery lesion and the severity of coronary atherosclerosis. Cathepsin K concentrations in patients with a high SYNTAX score of coronary atherosclerosis were shown to be 5.5 times lower in the presence of osteopenic syndrome (OPS) than in those with the similar severity of atherosclerosis and normal BMD. Analysis of osteopontin and CTX-I levels from the standpoint of the presence of OPS suggests that there are no differences in relation to both the type of coronary vessel lesion and its severity. Conclusion. Current data suggest that there are common mechanisms for the development of two socially significant conditions: atherosclerosis and osteoporosis (OP). The phenomenon of concomitant development of these diseases has been studied mainly in postmenopausal women. Today, however, OP is also increasingly found in men, associating with more severe manifestations of coronary atherosclerosis than in patients with no signs of osteopenia.